Peer navigators' role in supporting people living with human immunodeficiency virus in Australia: Qualitative exploration of general practitioners' perspectives. (7th June 2021) - Khalpey, Zoyah; Fitzgerald, Lisa; Howard, Chris; Istiko, Satrio Nindyo; Dean, Judith; Mutch, Allyson
Abstract: The redefining of human immunodeficiency virus (HIV) from an acute disease to a manageable chronic illness has reshaped the focus of care, emphasising clinical outcomes and sidelining the complex social barriers many people living with HIV (PLHIV) still face. This parallels changes in the location of HIV care in Australia, with many PLHIV seeking care from private general practitioners whose ability to address complex social issues is constrained by limitations of time and resources. In response, peer navigation has emerged as a model of care implemented by some HIV‐based community health organisations seeking to support PLHIV's biomedical and psychosocial needs. However, there is limited understanding of how peer navigation operates in community settings or of the way these programmes integrate with primary care. This paper is the first to explore peer navigation from the perspective of general practitioners (GPs), with experience in treating PLHIV, to understand the role they see for peer navigators (PNs) in supporting PLHIV. Semi‐structured in‐depth interviews were conducted with six GPs (11.5% of specialty HIV GPs in Queensland, Australia) to examine their views and experiences of peer navigation in the context of HIV care. GPs highlighted the complexities of care for PLHIV and the need for additional resources and supports for psychosocial care. GPs valued peer navigation as part of a patient support network and bridge to health and social care systems. PNs normalised HIV, alleviating fear and stigma, educating and translating clinical information for patients. However, a key challenge was the absence of direct communication pathways with PNs. Peer navigation has clear potential in supporting the care of PLHIV, to alleviate constraints in GP settings and expand HIV care beyond the clinic.